The Importance of Dermoscopy for Early Recognition of Superficial Spreading Melanoma in Adolescents: A Case Report - Cherry Chalik; Ennesta Asri; Indah Indria Sari (HM Publisher, 2025)
Background: Malignant melanoma, a highly aggressive form of skin cancer, is rare in adolescents. Early diagnosis is crucial for the best possible treatment and prognosis. Dermoscopy, a non-invasive technique, has been shown to increase the sensitivity of melanoma diagnosis, leading to early identification and better treatment outcomes. Case presentation: A 14-year-old female presented with a painful, bleeding black nevus on her right upper arm, increasing in size over four months. Dermoscopic examination, using a two-step algorithm and the ABCD rule, categorized the lesion as malignant melanoma. Histopathological examination confirmed the diagnosis of superficial spreading melanoma (Breslow 2, AJCC stage IIB). The patient underwent Mohs surgery for treatment. Conclusion: This case highlights the importance of dermoscopy in the early recognition of melanoma in adolescents. Dermoscopy aids in differentiating between benign and malignant melanocytic lesions, enabling prompt diagnosis and treatment. Increased awareness and utilization of dermoscopy can significantly improve outcomes in this patient population.